2010
DOI: 10.1111/j.1432-2277.2010.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of heme oxygenase-1 in transplantation

Abstract: Summary Heme oxygenase‐1 (HO‐1) is the rate‐limiting enzyme in heme catabolism that converts heme to Fe++, carbon monoxide and biliverdin. HO‐1 acts anti‐inflammatory and modulates apoptosis in many pathological conditions. In transplantation, HO‐1 is overexpressed in organs during brain death, when undergoing ischemic damage and rejection. However, intentionally induced, it ameliorates pathological processes like ischemia reperfusion injury, allograft, xenograft or islet rejection, facilitates donor specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 147 publications
1
35
0
1
Order By: Relevance
“…It has been demonstrated that HO-1 induces autophagy in a mouse model of liver IR injury; however, the specific mechanisms involved require further investigation (35). It has also been previously demonstrated that HO-1 protein expression is induced in injured cells or cells under stess (26)(27)(28). In our study, this was achieved by treatment with mineral oil, which caused damage to the liver cells due to the lack of nutrients and oxygen.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It has been demonstrated that HO-1 induces autophagy in a mouse model of liver IR injury; however, the specific mechanisms involved require further investigation (35). It has also been previously demonstrated that HO-1 protein expression is induced in injured cells or cells under stess (26)(27)(28). In our study, this was achieved by treatment with mineral oil, which caused damage to the liver cells due to the lack of nutrients and oxygen.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have shown that HO-1 plays a very important anti-inflammatory role in a number of inflammatory diseases, and it may act as an anti-apoptotic and anti-proliferative mediator for many damaged organs or cells under stress conditions (26)(27)(28). In liver cell injury, induced HO-1 preconditioning may lead to adaptive stress reaction, and may occur in response to organ ischemic insults, protecting the cells from injury (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 has antioxidant, antiapoptotic and anti-inflammatory effects (8) and improves outcomes for both islet allografts and xenografts (9,10). Tumor necrosis factor-a (TNF-a) is produced chiefly by activated macrophages, although it can be produced by other cell types such as CD4 þ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, induction of HSPs during stress diminishes with aging (74) and is associated with increased injury (75). The protective capacity of HSP-32, or hemeoxygenase 1 (HO-1), has been comprehensively reviewed elsewhere (76). Briefly, while not having a chaperoning function, HO-1 exhibits anti-inflammatory, anti-oxidant, and anti-apoptotic properties (77).…”
Section: Injury and Repair In The Aging Organmentioning
confidence: 99%